An Examination of the Intricacies and Potentialities of Interreligious and Interfaith Matrimonial Unions in Modern Times - Murshida Khatun; Md Amirul Islam; Md. Habibur Rahman; Md Ashraful Amin (HISTORICAL: Journal of History and Social Sciences, 2024)
This study looks at the challenges and benefits of interreligious and interfaith marriages. It looks at how different beliefs, values, and practices affect personal relationships and the way a family works. Using a qualitative research approach, we conducted in-depth investigations and research on interreligious and interfaith marriages to gain insight into the various measurements in different countries and religions. Interfaith marriage is prohibited in many religions, but in the present it is normal. Especially in Christianity, interfaith marriage is popular at differing ages, like before 25, 26–35, and 36–45, with a percentage of 48, 58, and 67. Our findings suggest that while these marriages can be challenging, they also offer opportunities for personal growth, greater understanding of different religious traditions, and the promotion of interfaith dialogue and cooperation.